Lime effects on the introduction of winter forage legumes - Macedo, Walfredo; Brasil, Nei Eduardo; Patella, José Francisco (Pesquisa Agropecuaria Brasileira, 2014)
Effects of rates and methods of lime application on the establishment of two winter forage legumes on native pasture were studied. Lime increased total dry matter yields up to 30% over that of the check treatment. It did not show any effect on yields of native grass species but it did increase the dry matter yields of legume species introduced in the mixture. Measured forage yields were not affected by application methods (i.e. only broadcasted vs. broadcasted and incorporated) neither by lime rate on the range from 2.5 to 4.0 t/ha.